Les risques conchylicoles en Baie de Quiberon. Deuxième partie : le risque de prédation sur l’huître creuse Crassostrea gigas. Rapport final du projet Risco 2010-2013 ... - Mazurie, Joseph; Stanisiere, Jean-Yves; Bouget, Jean-Francois; Langlade, Aime; Leclerc, Emilie; Quinsat, Kevin; Herve, Gilles; Augustin, Jean-Marie; Ehrhold, Axel; Sinquin, Jean-Marc; Meidi-Deviarni, Ika; Goubert, Evelyne; et al. (Ifremer, 2013)
This study (“Risco”), implicating both industry, socio-economic experts and biologists, was funded by the Regional Council of Brittany, for 3 years (2010-2012), to investigate about the causes of oysters (Crassostrea gigas) mortalities in the bay of Quiberon (South Brittany, France). The protocol including both a sonar and video visualization of the bottom, and a monthly survey of 15 experimental oyster structures, allowed to assess the risk due to predation. A clear spatial distribution of the predatory effect was evidenced, with starfish (Asterias rubens and Marthasterias glacialis) predominating in the North-East sector, and boring snails (Ocenebra erinacea and Pterophora inornata) in the South-Center area.. The main mortalities from these predators (3/4 from starfish and ¼ from oyster drills) occur in spring and summer. Mortalities by sea breams (Sparus aurata) were observed punctually. Management measures against predators appear essential to control this risk. However, another environmental factor, ... : L’étude « Risco » s’attache aux causes possibles de mortalités massives d’huîtres creuses, de toutes classes d’âge, enregistrées par les concessionnaires de baie de Quiberon (France, 56), à partir de 2006. Le protocole engagé en 2010, avec son volet expérimental fondé sur le suivi mensuel de 15 lots d’huîtres et son volet d’imagerie in situ par sonar et vidéo, permet d’éclairer en particulier le risque lié aux prédateurs. Une spatialisation très marquée de ce risque est mise en évidence, avec une zone à l’ouest relativement épargnée, une zone à l’est très affectée par les étoiles de mer (A. rubens, M. glacialis) et une zone intermédiaire à forte prédation de bigorneaux perceurs (O. erinacea, P. inornata). Entre ces deux groupes, la prédation est réalisée pour les ¾ par les étoiles de mer et pour ¼ par les bigorneaux. Les pertes maximales ont lieu au printemps (recrudescence d’étoiles de mer) et en été (efficacité maximale de prédation). La prédation par dorades, devenue très préoccupante ces dernières ...